Au–ZnO Conjugated Black Phosphorus as a Near-Infrared Light-Triggering and Recurrence-Suppressing Nanoantibiotic Platform against Staphylococcus aureus - Atanu Naskar; Sohee Lee; Kwang-sun Kim (Pharmaceutics, 2021)
Antibiotic therapy is the gold standard for bacterial infections treatment. However, the rapid increase in multidrug-resistant (MDR) bacterial infections and its recent use for secondary bacterial infections in many COVID-19 patients has considerably weakened its treatment efficacy. These shortcomings motivated researchers to develop new antibacterial materials, such as nanoparticle-based antibacterial platform with the ability to increase the chances of killing MDR strains and prevent their drug resistance. Herein, we report a new black phosphorus (BP)-based non-damaging near-infrared light-responsive platform conjugated with ZnO and Au nanoparticles as a synergistic antibacterial agent against Staphylococcus aureus species. First, BP nanosheets containing Au nanoparticles were assembled in situ with the ZnO nanoparticles prepared by a low-temperature solution synthesis method. Subsequently, the antibacterial activities of the resulting Au–ZnO–BP nanocomposite against the non-resistant, methicillin-resistant, and erythromycin-resistant S. aureus species were determined, after its photothermal efficacy was assessed. The synthesized nanocomposite exhibited excellent anti-S. aureus activity and good photothermal characteristics. The non-resistant S. aureus species did not produce drug-resistant bacteria after the treatment of multiple consecutive passages under the pressure of the proposed nanoantibiotic, but rapidly developed resistance to erythromycin. This work clearly demonstrates the excellent photothermal antibacterial properties of Au–ZnO–BP nanocomposite against the MDR S. aureus species.